Control condition design and implementation features in controlled trials: a meta-analysis of trials evaluating psychotherapy for depression - Mohr, David C (Transl Behav Med, 2014)
ABSTRACT: Control conditions are the primary methodology used to reduce threats to internal validity in randomized controlled trials (RCTs). This meta-analysis examined the effects of control arm design and implementation on outcomes in RCTs examining psychological treatments for depression. A search of MEDLINE, PsycINFO, and EMBASE identified all RCTs evaluating psychological treatments for depression published through June 2009. Data were analyzed using mixed-effects models. One hundred twenty-five trials were identified yielding 188 comparisons. Outcomes varied significantly depending control condition design (p < 0.0001). Significantly smaller effect sizes were seen when control arms used manualization (p = 0.006), therapist training (p = 0.002), therapist supervision (p = 0.009), and treatment fidelity monitoring (p = 0.003). There were no significant effects for differences in therapist experience, level of expertise in the treatment delivered, or nesting vs. crossing therapists in treatment arms. These findings demonstrate the substantial effect that decisions regarding control arm definition and implementation can have on RCT outcomes.